'Safety overrides all other concerns': On why collective discipline in China fail to rehabilitate female prisoners. (September 2022) - Zhang, Ao
Abstract: Although scholars have shown a continuing interest in probing the disciplinary nature of China's penal system, relatively few studies examine its 'collective' connotation of discipline and the effectiveness in achieving the primary target of Chinese imprisonment: rehabilitation. Drawing on interviews undertaken with 30 female parolees/ex-prisoners and 10 prison officers, this study argues that the collective discipline at selected prisons is a deepening and possible an extension of Foucauldian project. Yet, compliance and docility do not equate well rehabilitation. The findings suggest that rehabilitative interventions are implemented more for order and safety maintenance rather than eliciting deep contrition of prisoners. The rigorous political climate of increasing accountability further disrupts any ethos of rehabilitation. Officers' diligent and skilled use of control demonstrates a 'tactical agreement' that while prisoners as autonomous agents value their performances for early release, officers depend on the consent of the prisoners to get through the day.